Prevalence of haemosporidia in Asian Glossy Starling with discovery of misbinding of Haemoproteus-specific primer to Plasmodium genera in Sarawak, Malaysian Borneo - Vaenessa, Noni; Tan, Cheng Siang (Biomed Central, 2023)
Background Plasmodium, Haemoproteus and Leucocytozoon are three mainly studied blood parasites known to cause malarial and pseudomalarial infections in avian worldwide. Although Sarawak is a biodiversity hotspot, molecular data on blood parasite diversity in birds are absent. The objective of the study is to determine the prevalence of blood parasite in Asian Glossy Starlings (AGS), an urban bird with high population density in Sarawak and to elucidate the phylogenetic relationship with other blood parasite.